IMPROVEMENT OF QUALITY INDICATORS OF THE SPATIAL TRACKING SYSTEM WITH SCANNING - Sergey Vladimirovich Bystrov; Alexander Borisovich Bushuev; Valery Vladimirovich Grigoriev; Olga Karybekovna Mansurova; Ivan Mitrofanovich Pershin (Современная наука и инновации)
The main result of the method of improving the quality of spatial tracking systems with scanning is to improve the accuracy and reliability of tracking by taking into account the discrete dynamics of the drive control system, especially between the premises of sounding pulses. The drive control signal is formed in the form of linear stationary feedbacks on the coordinates of the drive state, the feedback coefficients are changed synchronously with the sequence of sounding pulse parcels and periodically with the scanning period of the antenna directivity diagram, and the scanning of the antenna directivity diagram is synchronized with the sequence of sounding pulse parcels.